Community perspectives on sustaining a Vulture Safe Feeding Site - Saru Thapa Pandey; Ramji Gautam; Hari Prasad Sharma (Global Ecology and Conservation)
Vulture Safe Feeding Sites (VSFSs) were established to provide diclofenac-free carcasses to vultures after identifying that the drug was the primary cause for the vulture population decline in south Asia. However, the long-term sustainability of these VSFSs is uncertain. To assess this, we conducted a questionnaire survey in 2022 to evaluate the willingness of local communities in Gaidahawa, to provide old and unproductive cows to the VSFS. This VSFS is of crucial importance, as it supports seven vulture species. A total of 310 people in the vicinity of the VSFS participated in the questionnaire surveys. Among the total households with livestock, only a small proportion (17 %) of respondents expressed their willingness to contribute old cow to the VSFS. We found that local peoples’ perceptions of the VSFS varied based on their proximity to the site (ꭓ2 = 37.35, df = 2, p < 0.001). Our study suggests inadequate management of the VSFS in Gaidahawa, potentially leading to challenges in acquiring old cows to sustain the site in the future. Therefore, we recommend that VSFS managers take steps to encourage local residents to contribute old cows by assisting them to transport the animals to the site, develop a management plan, and raise awareness for the conservation of vultures. These measures are crucial for ensuring the sustained operation and success of the VSFS, ultimately contributing to vulture conservation efforts in the region.